The influence of social influence, habit, and price value on use behavior of streaming applications among gen z using the utaut2 model - Kusumaningtias, Evita Nurliana; i Lestari, Wuryaningsih Dw (Institute of Computer Science (IOCS), 2025)
This research, titled